PERANAN KYAI DALAM PENGEMBANGAN PENDIDIKAN FORMAL DI PESANTREN (Studi Kasus di Pesantren Darussalam Blokagung, Tegalsari, Banyuwangi) - Al Muftiyah (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2013)
In the history of the oldest educational institutions inIndonesia is the school and the holder of the highest role in it wasa teacher of Islam. A religious scholars not only as a central pointof all activities at the school, but also as a religious teacher, acharacter, giving an example to all the people around him.Existence of Formal Education at Pesantren DarussalamBlokagung, in its management of education in the foundationPesantren Darussalam Blokagung is adhering to the maqolah